2018
DOI: 10.1063/1.5052434
|View full text |Cite
|
Sign up to set email alerts
|

Generation of rogue waves in space dusty plasmas

Abstract: The basic features of dust-acoustic (DA) waves (DAWs) in four component dusty plasma system (containing inertial cold and hot dust grains, inertialess non-extensive ions and electrons) have been theoretically investigated by deriving the nonlinear Schrödinger equation. The analytic analysis under consideration demonstrates two types of modes, namely, fast and slow DA modes. The unstable domain for the fast DA mode, which can be recognized by the critical wave number (k c ), gives rise to the DA rogue waves (DA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…To study IASHWs, we derive Burgers' equation by employing the reductive perturbation method (RPM) [36,37], and the stretched coordinates for independent variables can be written as [38,39,40]…”
Section: Derivation Of the Burgers' Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…To study IASHWs, we derive Burgers' equation by employing the reductive perturbation method (RPM) [36,37], and the stretched coordinates for independent variables can be written as [38,39,40]…”
Section: Derivation Of the Burgers' Equationmentioning
confidence: 99%
“…ions in astrophysical compact objects (viz., white dwarfs and neutron stars) has received a substantial attention to investigate ion-acoustic (IA) waves (IAWs) in degenerate quantum plasma (DQP). The particle number density in the white dwarfs (i.e., 6×10 29 cm −3 ) and neutron stars (i.e., 6×10 36 cm −3 ) is extremely high [1,9,11,13]. This extreme number density of these degenerate particles dictates to follow the Heisenberg's uncertainty principle, and according to the uncertainty principle when the position of these particles is confined then the momentum of these particles tends to very large.…”
Section: Introductionmentioning
confidence: 99%
“…The plot of P/Q against k yields stable and unstable parametric regimes of the DAWs. The point, at which the transition of P/Q curve intersect with k-axis, is known as threshold or critical wave number k (= k c ) [18,19,20,21,22,23,24,25]. The governing equation for highly energetic DARWs in the modulationally unstable parametric regime (P/Q > 0) can be written as [26,27,28,29,30]…”
Section: Modulational Instability and Rogue Wavesmentioning
confidence: 99%
“…Vasylinaus [25] first demonstrated the super-thermal κdistribution for explaining the high energy tails which can be observed in the non-equilibrium plasma systems [26,27,28,29], and introduced the parameter κ in the superthermal κ-distribution for measuring the amount of deviation of the plasma species from Maxwell-Boltzmann distributions. Kaladze and Mahmood [26] investigated the nonlinear features of IAWs in a super-thermal plasma, and observed that the superthermal electrons can cause to decrease the height of the IAWs.…”
Section: Introductionmentioning
confidence: 99%